Decadal changes in rapid intensification of western North Pacific tropical cyclones modulated by the North Pacific Gyre Oscillation - Jinjie Song; Philip J Klotzbach; Yifei Dai; Yihong Duan (Environmental Research Communications, 2023)
This study investigates the modulation of western North Pacific (WNP) tropical cyclone rapid intensification (RI) by the North Pacific Gyre Oscillation (NPGO) on decadal timescales. There is a significant inverse relationship between basinwide RI numbers during July–November and the simultaneous NPGO index from 1970 to 2021. During the positive NPGO phase, suppressed RI occurs over almost the entire WNP, with a distinctly different spatial distribution compared to the Pacific Decadal Oscillation-driven pattern of RI modulation. RI occurrence is significantly reduced over the eastern Philippine Sea (10°–25°N, 140°–155°E). This is primarily caused by enhanced negative low-level vorticity, which can be linked to the horizontal extent of the anomalous low-level anticyclone. By comparison, over the western Philippine Sea (10°–25°N, 125°–140°E), there are only weak RI occurrence changes due to offsetting influences of increased mid-level humidity and decreased low-level vorticity.